(untitled) (CAHIERS MAGELLANES-NS, 2024)
The use of AI in arbitration processes can be viewed as one of the most effective ways to change the outcomes of disputes as well as the approaches used to solve them by increasing their efficiency and reducing the bills and errors in this sphere. This paper is therefore titled: Optimizing Arbitration Processes through Artificial Intelligence; it analyses the way that Artificial Intelligence is now having a positive influence on many processes involved in arbitration, including case assessment, case analysis, case hearings and the enforcement of awards. The work starts with the examination of such opportunities as AI-based legal tech tools for conducting research and document analysis with the emphasis on the ability to quickly process large amounts of data and select the necessary precedents. It also reviews case management and more specifically how AI can help with scheduling, task assignment, and monitoring of the cases’ progress, which saves time and eliminates the extra paperwork and slowness that could occur otherwise. Furthermore, it outlines the use of foresight in arbitration where artificial intelligence can calculate a case’s outcome using past determinations in an effort to assist the parties make wiser choices. The possibility of introducing innovations in the handling of evidence by means of improving the types and methods of e-discovery tools and methods of using AI for the organization of evidence is also considered. In addition, the study also covers AI’s role in virtual hearings and remote arbitration by maintaining cooperation and effective communication notwithstanding the geographical location differences.However, the paper also regulates the problems and threats of AI implementation in arbitration, including data protection complications, ethical questions, and require human intervention. Success stories and right AI use cases are adopted from industries, and the policy suggestions are focused on judicial education, effective policies, and the advancement of technology.It is with this understanding that this paper seeks to map out areas of application for arbitration while outlining its strengths and weaknesses with the goal of formulating concrete recommendations for the systematic enhancement of this key proceeding. The study emphasises the importance of an affair that follows the merits of AI implementation, and at the same time addresses the issue of system integrity within arbitration.